Pengaruh Influencer Marketing Terhadap Purchase Decision dengan Brand Awareness dan Perceived Value Sebagai Variabel Mediasi - Ismawati Ismawati; Lutfi Lutfi; Enok Nurhayati (MANAJEMEN, 2025)
This study aims to explore the influence of Influencer Marketing on Purchase Decision with Brand Awareness and Perceived Value as mediating variables for Purbasari scrub users in Cilegon City. The research method used is quantitative. This research collects data based on questionnaires and literature studies. The population in this study were Purbasari scrub users in Cilegon City. The sample of this study amounted to 180 respondents with accidental sampling. The data analysis method used is Structural Equation Modeling (SEM) with the SmartPLS 4 analysis tool. The results of this study indicate that Influencer Marketing has a positive but insignificant effect on Purchase Decision. Furthermore, Brand Awareness and Perceived Value are found to mediate the relationship between Influencer Marketing and Purchase Decision. In this study, Brand Awareness and Perceived Value demonstrate the ability to strengthen the effect of Influencer Marketing on Purchase Decision.